Laminin as a Potent Substrate for Large-Scale Expansion of Human Induced Pluripotent Stem Cells in a Closed Cell Expansion System - Fernanda C. Paccola Mesquita; Camila Hochman-Mendez; Jacquelynn Morrissey; Luiz C. Sampaio; Doris A. Taylor (Stem Cells International)
The number of high-quality cells required for engineering an adult human-sized bioartificial organ is greater than one billion. Until the emergence of induced pluripotent stem cells (iPSCs), autologous cell sources of this magnitude and with the required complexity were not available. Growing this number of cells in a traditional 2D cell culture system requires extensive time, resources, and effort and does not always meet clinical requirements. The use of a closed cell culture system is an efficient and clinically applicable method that can be used to expand cells under controlled conditions. We aimed to use the Quantum Cell Expansion System (QES) as an iPSC monolayer-based expansion system. Human iPSCs were expanded (up to 14-fold) using the QES on two different coatings (laminin 521 (LN521) and vitronectin (VN)), and a karyotype analysis was performed. The cells were characterized for spontaneous differentiation and pluripotency by RT-PCR and flow cytometry. Our results demonstrated that the QES provides the necessary environment for exponential iPSC growth, reaching 689.75 × 106 ± 86.88 × 106 in less than 7 days using the LN521 coating with a population doubling level of 3.80 ± 0.19. The same result was not observed when VN was used as a coating. The cells maintained normal karyotype (46-XX), expressed pluripotency markers (OCT4, NANOG, LIN28, SOX2, REX1, DPPA4, NODAL, TDGFb, TERT3, and GDF), and expressed high levels of OCT4, SOX2, NANOG, SSEA4, TRA1-60, and TRA1-81. Spontaneous differentiation into ectoderm (NESTIN, TUBB3, and NEFH), mesoderm (MSX1, BMP4, and T), and endoderm (GATA6, AFP, and SOX17) lineages was detected by RT-PCR with both coating systems. We conclude that the QES maintains the stemness of iPSCs and is a promising platform to provide the number of cells necessary to recellularize small human-sized organ scaffolds for clinical purposes.